Bioarchaeological evidence for the health status of a Late Bronze Age and Early Iron Age Bakheri chala population (Armenia) - Khudaverdyan, Anahit Yu; Hobossyan, Suren G (Anthropologie, 2017)
Thirty-two skeletons from burial ground Bakheri chala were analysed macroscopically and X-ray for pathological conditions such as trepanation, traumatic injuries, infectious disease and dental pathology. This study has shown that average age at death was relatively high. Trepanation with rectangular sawing for the first time found in the Armenia at two individuals. Trauma to the skull was common, which suggests a high level of inter-personal violence. We here report a case of decapitation. Bakheri chala site showed a high frequency of auditory exostosis. The dental pathology conditions of this population were numerous. Agriculture introduced people to carbohydrates, or sugars, which affect the teeth and cause dental caries. The staple diet of ancient population from Shnogh river consisted of wine, bread, vegetables, and fruits. Males do show a slightly higher rate of wear than females possibly suggesting a greater proportion of bread in the diet of males.
Keywords: Communicable Diseases; archeologie; Armenia; trepanace; Exhumation; Tooth Diseases; Body Remains; Health Status; lidé; zdravotní stav; Trephining; Craniocerebral Trauma; infekční nemoci; kraniocerebrální traumata; dějiny starověku; Arménie; Archaeology; nemoci zubů; exhumace; tělesné pozůstatky; History, Ancient; Humans